The role of RhoH in TCR signalling and its involvement in diseases - Ahmad Mokhtar, Ana Masara; Hashim, Ilie Fadzilah; Zaini Makhtar, Muaz Mohd; Salikin, Nor Hawani; Amin Nordin, Syafinaz (MDPI, 2021)
As an atypical member of the Rho family small GTPases, RhoH shares less than 50% sequence similarity with other members, and its expression is commonly observed in the haematopoietic lineage. To date, RhoH function was observed in regulating T cell receptor signalling, and less is known in other haematopoietic cells. Its activation may not rely on the standard GDP/GTP cycling of small G proteins and is thought to be constitutively active because critical amino acids involved in GTP hydrolysis are absent. Alternatively, its activation can be regulated by other types of regulation, including lysosomal degradation, somatic mutation and transcriptional repressor, which also results in an altered protein expression. Aberrant protein expression of RhoH has been implicated not only in B cell malignancies but also in immune-related diseases, such as primary immunodeficiencies, systemic lupus erythematosus and psoriasis, wherein its involvement may provide the link between immune-related diseases and cancer. RhoH association with these diseases involves several other players, including its interacting partner, ZAP−70; activation regulators, Vav1 and RhoGDI and other small GTPases, such as RhoA, Rac1 and Cdc42. As such, RhoH and its associated proteins are potential attack points, especially in the treatment of cancer and immune-related diseases.